Incidence and severity of aphid-transmitted viruses and horticultural performance of habanero pepper (Capsicum chinense Jacq.) breeding lines in Benin - Zohoungbogbo, Herbaud P.F.; Achigan-Dako, Enoch G.; Honfoga, Judith; Lin, Shih-Wen; Lin, Tsung-Han; Wang, Yen-Wei; Chan, Yuan-Li; Hanson, Peter; Barchenger, Derek W. (American Society for Horticultural Science, 2022)
Habanero (Capsicum chinense Jacq.) is widely grown and consumed in West and Central African countries, and viral diseases represent an important production challenge. Diagnosis of the viral species affecting habanero productivity in Benin is limited, and understanding this will enable more efficient host resistance breeding. During 2019 and 2020, we characterized the incidence and severity of the viral diseases infecting nine promising habanero breeding lines and one commercial hybrid check under open field conditions in Benin. The horticultural performance, including yield and yield component traits of the entries, was determined during the 2 years of the experiment. A randomized complete block design was used with three replications, each with 24 plants. Data were recorded on days to 50% flowering and 50% fruit maturity, yield and on the yield components of fruit weight (g), fruit length (cm), and fruit width (mm), as well as disease incidence and severity. In total, 35 leaf samples were collected for viral diagnosis among habanero breeding lines. We found that Pepper veinal mottle virus (PVMV; Potyvirus) was the overwhelmingly predominant virus in our trials, with an 80% incidence; however, we found frequent coinfection of PVMV with Cucumber mosaic virus (CMV, Cucumovirus), Polerovirus, and, to a lesser extent, Chili veinal mottle virus (ChiVMV; Potyvirus). The mean disease incidence across all entries was 60%. AVPP1932 and PBC 2010 had the lowest disease incidence (35% and 43%, respectively), whereas AVPP1929 had the highest (86%) disease incidence. The F1 hybrid check Afadja had the overall highest yield, with 30 t⋅ha−1, followed by AVPP1932, with 19 t⋅ha−1, both in 2019. There was a negative correlation between disease incidence and total yield (r = −0.44; P < 0.001), supporting previous studies indicating that viral diseases are major production constraints for habanero in West Africa. This study provides insight regarding the need to improve habanero for resistance to aphid-transmitted viruses and develop integrated pest management strategies to limit losses in Benin.